Study of Fungal Contamination of Indoor Public Swimming Pools - H Nanbakhsh; K Diba; K Hazarti (Tehran University of Medical Sciences, 2004)
Fungi are found in different environments with variable distribution patterns depending on various factors. The aim of this study was determination of fungal contaminants in public swimming pools in Uromia, Iran. The fungal contaminations of four indoor swimming pools were studied by using membrane filtration and swab sampling method. Samples were collected by a manual plastic pump, in a 200 ml sterilized bottle. All samples were collected within 2 hours and then transferred to the laboratory. A total of 384 samples including water and environmental surfaces were collected and tested for the presence of fungi in different seasons within one year. In addition to the above information, some physical and chemical parameters such as temperature, residual chlorine, pH, turbidity of water and the number of swimmers were studied. Findings indicated that, the average temperature, pH, residual chlorine and turbidity of water in the swimming pools within one year were: 29.9°C, 8.1, 0.6 ppm and 0.8 NTU respectively. The most common fungi recovered were as follows: Asepergillus Spp. 56.25%, Candida spp. 22.9%, Rhizopus spp. 4.16 %, other filamentous fungi 16.6% and other yeast species 2.8%. The fungi such as Alternaria, Cladosporium, Philophora and Trichophyton mentagrophytis were isolated from dressing room, bathing room and other places out of pools. According to these results and previous studies on pools, it has been indicated that contamination by fungi in the pools is not significant in water and environment. Presence of dermatophytic fungus from dressing room is probably due to human contact.